PEMBELAJARAN ANALISIS MORFOLOGIS DALAM TEKS BIOGRAFI MENGGUNAKAN METODE PEMBELAJARAN TANDUR PADA PESERTA DIDIK KELAS X SMK PELITA - Mia Suminar (STKIP Subang, 2022)
The purpose of this study was to describe the improvement of learning outcomes of biograpy texts, writing skills and analysis of morphological processes using the TANDUR learning method in class X SMK Pelita. TANDUR learning method is an acronym for Grow, Experience, Name, Demonstrate, Repeat and Celebrate. The research method used is a quasi-experimental class consisting of a control class and an experimental class, both classes will carry out pretest and posttest activities. Each class consisted of approximately 45 people, but in each experimental class and control class, samples were taken from each control and experimental class with a total of 30 students. When the normality test and homogeneity test were carried out using the Leavene test in biographical text learning, the data were normal and homogeneous, the results of the n-gain t-test calculation using the independent sample t-test the results showed 0.000 less than 0.05, it can be concluded that there is an increase which is significant between the learning outcomes of the experimental class and the control class. When the normality test and homogeneity test were used, the data was not normal and not homogeneous, so a non-parametric test using Mann-Withney was used, the result was 0.005 smaller than 0.05, which means there was an increase in the ability to write biographical texts in the experimental class and control class. So it can be concluded that the TANDUR learning method can improve learning outcomes and writing biograpy text skills in class X SMK Pelita. Keywords: Keywords: Learning, Biographical Text, TANDUR learning method.